Reviewing the (shrinking) principle of trademark exhaustion in the European Union (ten years later) - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2012)
Ten years ago, I published an article in the Marquette Intellectual Property Law Review titled “Trademark Exhaustion in the European Union: Community-Wide or International? The Saga Continues.” In that article, I described the development of the principle of trademark exhaustion in the European Union (EU) and analyzed the interplay among trademark protection, trademark territoriality, and the treatment of the parallel importation of gray market products—unauthorized genuine goods imported from foreign countries—under Article 7 of the Trademark Directive (Article 7). In this Essay, I continue to explore, ten years after my 2002 article, the development of the principle of trademark exhaustion in the EU. In particular, I analyze the recent jurisprudence of the CJEU on the application of Article 7 and recount the most relevant trends in the recent CJEU’s decisions in this area. Although the focus of this Essay is primarily descriptive, I offer some critical considerations in the light of recent CJEU’s decisions. I thus argue that in its recent line of cases, the CJEU seems increasingly willing to shrink, de facto, the application of the principle of trademark exhaustion not solely to products imported from outside the EEA, but also to intra-EEA trade. Most notably, I highlight that the CJEU seems to have accepted a narrow interpretation of the notion of trademark owners’ “consent” under Article 7(1) of the Trademark Directive. I also argue that the CJEU seems to have adopted an alarmingly broad interpretation of what can constitute a “legitimate reason” to oppose trademark exhaustion under Article 7(2), especially to protect famous marks and luxury goods against unauthorized trade by third party importers, still within the EEA. This trend, I conclude, is troubling and may negatively impact the principle of free movement of goods within the EU/EEA. Furthermore, it grants trademark owners (primarily the owners of famous marks) an increasingly absolute right to control the distribution of their marked products in the after-sale market—precisely what the principle of trademark exhaustion was designed to prevent—to the detriment of consumers and market competition.